PRODUKSI INDIE FILM TUTORIAL TARI GAMBYONG PAREANOM - Siswanta, Aris Triharyanto & Maya Sekarwangi (Universitas Slamet Riyadi, 2017)
Along with the development of modern society characterized by advanced technology, the existence of the art of classical dance began to marginalised by contemporary art and culture. One of the efforts to preserve the art and culture of classical dance, the producer of the film and television industry is starting to give the access the classic dance art event in the film and television program. The method used with the approach of learning by doing. The method is intended to involve the active participation of the entire members of the target group in the overall process of film making tutorial classical dance at both the pre production process, production and post- production processes. All the actors and crew involved in the making of the film is taken from a member of the Pokdarwis team consists of the same shared IbM. Ibm's activities results in improving the quality of human resources is more competent in the field of cinema art and develop art skills of making film script, operationalize the camera and editing skills.Keywords: Tutorial, classical dance, movie